Catholic Universities in an Increasingly Competitive Environment. Issue 1 (2nd January 2023) - Wodon, Quentin
Abstract: Pope Francis' vision for a global compact on education, including the role that Catholic universities should play, is in sharp contrast to the vision that dominates the higher education sector: that of producing graduates for gainful employment. Can Catholic colleges and universities rise to the challenge? This article provides a partial answer to that question by first considering four trends affecting higher education globally: (i) the impact of Covid; (ii) the technologization of higher education; (iii) the promise of employability; and (iv) the great unbundling towards micro-credentials. Thereafter, using data for the United States, the article provides a brief assessment of whether Catholic universities may be losing ground, while nevertheless keeping some sources of comparative advantage. The analysis remains explorative and tentative. What seems clear is that there is a lot of heterogeneity between institutions, with some struggling and others finding ways to maintain their comparative advantages.